Students' Mathematical Connection Ability in Solving Block and Prism Problems viewed from Cognitive Style - Rakhmawati, Astri; Hidayati, Herlina; Hari Putra, Yusuf Guntur (Jurnal Ilmiah Mandala Education (JIME), 2024)
Mathematical connection skills are very necessary in solving flat-sided geometric problems. This research aims to describe the mathematical connection abilities of class VIII students at SMP Negeri 11 Sampit in solving cubaid and prism problems in terms of cognitive style. This research uses a qualitative-descriptive approach. The subjects in this research consisted of cognitive style subjects’ field dependent (FD) 1 student and cognitive style subjects’ field independent (FI) 1 student. The instruments used in this research were the GEFT test, mathematical connection ability test and interviews the results of this research show that the mathematical connection ability in solving flat-sided geometric problems of FD cognitive style subjects has difficulty in connecting between concepts, is slow in making decisions and is less analytical. Mathematical connection abilities in solving flat-sided geometric problems, FI cognitive style subjects are able to connect and analyze concepts, and are able to categorize them into a plan. These results show that there are differences in students' mathematical connection abilities in solving flat-sided geometric problems in terms of cognitive style.